Crossing Among Sixteen Sweet Potato Parents for Establishing Base Populations Breeding - Sri Umi Lestari; Ricky Indri Hapsari; Nur Basuki (AGRIVITA, Journal of Agricultural Science, 2019)
The base - population of the controlled cross breeding is one of the important factors to develop a new improved cultivar. Since the incompatible nature of sweet potato remains a barrier for genetic improvement, therefore it requires a lot of crossed pairs. This study aimed to determine the level of incompatibility among crossing line between high yielding and micronutrient content cultivars. The field experiment conducted at Brawijaya University Research Station, Jatikerto-Malang, during February to August 2015. The North Carolina Design II was applied to sixty pairs controlled cross breeding and their sixty reciprocal pairs of six cultivars for micronutrient content enrichment with ten high yielding cultivars. The observations were made to the cross flowers number, capsules, fruit sets, and seeds number. The level of incompatibility between crossed pairs was determined by the level of fruit set. The result showed that most pairs were compatible (fruit set > 20%) and only few were incompatible (fruit set < 10%). Among six parents with micronutrient content enrichment, two of them, have a high compatibility as as female parents, to all the high yielding cultivars, i.e. BIS OP-61 and Cangkuang. Positioning as a female parent can improve the effectiveness of its selection scheme.